Diabetes is associated with genotypically drug-resistant tuberculosis. Issue 3 (19th March 2020) - Ruesen, Carolien; Chaidir, Lidya; Ugarte-Gil, Cesar; van Ingen, Jakko; Critchley, Julia A.; Hill, Philip C.; Ruslami, Rovina; Santoso, Prayudi; Huynen, Martijn A.; Dockrell, Hazel M.; Moore, David A.J.; Alisjahbana, Bachti; et al.
Diabetes is associated with failure of tuberculosis (TB) treatment, but it is unclear whether this is related to genotypic drug resistance of the infecting mycobacteria. We used whole genome sequencing (WGS) to examine 1365 known drug resistance mutations in 896 Mycobacterium tuberculosis isolates from TB patients that were screened for diabetes using HbA1c testing as part of the TANDEM project [1]. Ethical approval was received from the London School of Hygiene and Tropical Medicine and institutional review boards in Indonesia and Peru. In Peru we selected all available M. tuberculosis isolates from TANDEM patients (44 with and 445 without diabetes), and in Indonesia we selected all available isolates from diabetic patients (n=115) plus a subset of isolates from non-diabetic patients (n=292) from the same clinics, during the same time period, frequency-matched by age. We used TB Profiler version 0.3.8 [2] to determine M. tuberculosis lineage and drug resistance. A phylogeny was constructed using PhyML version 3.0 [3], and the minimum pairwise distance for isolates was calculated separately for patients with and without diabetes, stratified by country. In a study in Peru and Indonesia, diabetes was associated with an increased risk of tuberculosis caused by Mycobacterium tuberculosis strains with resistance mutations, particularly against rifampicin, and this was not explained by previous TB treatment http://bit.ly/2QCvUEM